Sarcopenia and lower urinary tract diseases: links, mechanisms, and clinical implications - Liu, Shanyu; Cao, Hongliang; Wang, Liming; Li, Shuxin; Liang, Yuwei; Feng, Yubo; Gao, Zihan; Wang, Song; Lian, Xin (Frontiers in Nutrition, 2025)
Lower urinary tract diseases (LUTDs), including lower urinary tract symptoms (LUTS), overactive bladder (OAB), urinary incontinence (UI), bladder cancer (BC), prostate cancer (PCa), and benign prostatic hyperplasia (BPH), severely impair the quality of life of the elderly. Emerging evidence highlights a strong association between sarcopenia (progressive loss of muscle mass, strength, and function) and the prevalence, severity, and progression of LUTDs, as well as poorer treatment responses in affected patients—though most supporting studies are cross-sectional or retrospective, with prospective trials needed to confirm causality. Potential mechanisms linking sarcopenia to LUTDs include pelvic floor muscle weakening, neuromuscular dysfunction, metabolic/endocrine disturbances, genetic factors, and gut microbiome dysregulation. Clinically, interventions such as resistance exercise, nutritional support, gut microbiome-targeted strategies, pelvic floor training, and pharmacological therapies show promise in mitigating LUTDs symptoms by targeting sarcopenia. Integrating sarcopenia assessment into LUTDs management could improve patient care; future research should prioritize large-scale prospective trials to validate causal relationships, clarify key mediating mechanisms (e.g., specific gut microbial taxa, neuromuscular signaling pathways), and develop personalized intervention protocols tailored to distinct LUTD subtypes and patient characteristics.